Achievement of gifted adolescents in Singapore : the effects of perception, creative-thinking ability and an intervention programme "knowledge/volition/action" - Teo, Chua Tee. (2009)
This study hypothesizes that intellectually gifted adolescents in the Gifted Education Programme who had greater preferences for perception and creative-thinking would tend to perform less well academically owing to a lack of volition, and that an educational intervention encompassing self-knowledge, volition, consultation, time and stress management would result in significant improvements in achievement. The relationships between academic achievement, perception and creative-thinking ability were first ascertained using linear regression analyses. Gifted pupils who were interested in self-development were then randomly selected and randomly assigned to experimental and control groups. Experimental and control subjects were matched by age, sex, school, class, race, socio-economic status, creative-thinking ability, academic and non-academic achievement. The experimental effects on academic and non-academic achievement were reported using paired / tests, single-subject time series designs and interviews with subjects. Atypical cases of subjects who evinced remarkable, moderate and low personal gains were featured in case studies.